Cardiovascular disease risk burden in primary Sjögren's syndrome: results of a population‐based multicentre cohort study. (3rd February 2015) - Bartoloni, E.; Baldini, C.; Schillaci, G.; Quartuccio, L.; Priori, R.; Carubbi, F.; Bini, V.; Alunno, A.; Bombardieri, S.; De Vita, S.; Valesini, G.; Giacomelli, R.; et al.
Abstract Objective Systemic autoimmune diseases, in particular systemic lupus erythematosus and rheumatoid arthritis, are characterized by a high risk of premature cardiovascular (CV) events. Disease‐related characteristics and traditional CV disease risk factors may contribute to atherosclerotic damage. However, there are limited data on the risk of overt CV events in primary Sjögren's syndrome (pSS). Methods We retrospectively analysed a cohort of patients with 1343 pSS. Disease‐related clinical and laboratory data, traditional CV disease risk factors and overt CV events were recorded. Prevalence of traditional CV disease risk factors and of major CV events was compared between a subgroup of 788 female patients with pSS aged from 35 to 74 years and 4774 age‐matched healthy women. Results Hypertension and hypercholesterolaemia were more prevalent, whereas smoking, obesity and diabetes mellitus were less prevalent, in women with pSS than in control subjects. Cerebrovascular events (2.5% vs. 1.4%, P = 0.005) and myocardial infarction (MI) (1.0% vs. 0.4%, P = 0.002) were more common in patients with pSS. In the whole population, central nervous system involvement (odds ratio (OR) 5.6, 95% confidence interval (CI) 1.35–23.7, P = 0.02) and use of immunosuppressive therapy (OR 1.9, 95% CI 1.04–3.70, P = 0.04) were associated with a higher risk of CV events. Patients with leucopenia had a higher risk of angina (P = 0.01). Conclusions pSS is associated with an increased risk of cerebrovascular events and MI. Disease‐related clinical and immunological markers may have a role in promoting CV events.